Pengembangan Komik Sastra Sebagai Media Pembelajaran Siswa - Sahri Nova Yoga (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
This research aims to develop literary comic media as a learning medium for middle school students, produce viable comic products, and determine the differences in the results of applying comic media in experimental classes and control classes. This research uses a Research and Development research design. The trial was carried out at SMPN 3 Medan and SMPN 5 Medan. This trial use used True Experimental Design class VII-D at SMPN 3 Medan and class VII-A at SMPN 5 Medan. The instruments given were a product needs questionnaire with 14 questions and a test with 2 questions. Data analysis used the independent t-test which contained a difference test between 2 independent samples and hypothetically used the Mann Withney test which found differences in the independent learning outcomes of junior high school students between using comic media and not using comic media. This is proven from the results of the Mann Withney test calculations, so it can be concluded that there are differences in learning outcomes for junior high school students, and literary comic media is suitable for use as a learning medium. It is hoped that the results of this research can be used by related parties, such as teachers, students and future researchers